Les Gherardi, mouleurs à Paris et à Rome - Peter Malone (In Situ)
An account of the Gherardi family, 19th century castmakers with particular emphasis on Michele Gherardi from their commercial origins in Paris to international status at Rome, eventually merging with the long established firm of Malpieri.